Answer:
y=0, x=1
Step-by-step explanation:
6x-3y= -6 ...... equation 1
y =2x+2 ..... equation 2
subtract 2x from both sides
y-2x=2x-2x+2
y-2x=2
6x-3y= -6
y-2x=2
Rearrange
6x-3y= -6 ........x1
-2x +y=2............x3
6x-3y= -6
-6x +3y=2
0y=0
y=0
substitute y=0 in equation 1
6x-3xo= -6
6x= -6
x-6/6
x = -1
Answer:
f(n) = 1750 + 70n
Step-by-step explanation:
Since, each of them are depositing 35$ each month, they are adding 35x2 = 70$ each month.
So, in n months, they will be adding 70n $ to their account.
Initially, they had 1,750$ in their account. After n months, they should have 1750+70n $ in their account.
So, the function that represents this is, f(n) = 1750 +70n
Answer:
the picture isnt popping up
Yes, that is the famous first Pythagorean triplet: 3²+4²=5²
or
For three lengths to be able to form a triangle, it suffices that every one of those lengths is shorter than the sum and longer than the difference of the other two.
It is enough to check just one side.
So,
3 + 4 > 5
4 - 3 < 5
Your triangle is constructible.
The answer to your question is 11